392. Evaluation of the Long-Term Tolerability and Efficacy of Fluconazole in Patients With Coccidioidomycosis. (26th November 2018) - Davis, Matthew
Abstract: Background: Invasive fungal infections within the United States continue to increase annually and represent a significant cause of morbidity and mortality. Fluconazole is a first-generation triazole antifungal used in the treatment of several fungal infections including coccidioidomycosis. Treatment guidelines for coccidioidomycosis recommend high-dose fluconazole and severe or disseminated infections frequently require greater than 1 year of therapy. Although the toxicity profile of fluconazole has been evaluated in clinical trials, there is a paucity of data regarding the tolerability of this agent with long-term therapy. Methods: We conducted a single-center, retrospective study of adult patients (≥18 years) with proven or probable coccidioidomycosis between 2010 and 2018 receiving long-term fluconazole therapy for an intended duration of 28 days or greater. Outcomes: (1) Incidence and type of adverse events. (2) Result of adverse event on treatment course. (3) Association between adverse events and therapeutic drug levels. (4) Association between adverse events and fluconazole dose. (5) Efficacy of fluconazole therapy via modified Mycoses Study Group criteria. Sample: (1) 165 patients identified; (2) 42 excluded for not receiving long-term fluconazole; (3) 22 excluded with lack of documented coccidioidomycosis or long-term fluconazole; (4) 3 excluded for insufficient follow-up. Results: Out of 165 patients identified, 98 were included for analysis. Forty-eight patients (48.9%) experienced adverse effects directly attributed to fluconazole therapy by the evaluating physician. The most common adverse effects were xerosis (19.4%), alopecia (16.3%), fatigue (10.2%), and arthralgia (6.1%). Twenty-nine patients (29.5%) experienced adverse effects requiring therapeutic intervention such as dose reduction, discontinuation, or switch to new antifungal. The median therapeutic drug levels did not significantly differ between patients who experienced adverse effects from those who did not (30.5 μg/mL vs. 27.2 μg/mL; P = 0.5). Conclusion: A considerable proportion of patients experienced toxicity during anticipated long-term fluconazole therapy. With this information, providers will be able to identify toxicities associated and utilize alternative agents where necessary. Disclosures: All authors: No reported disclosures.